SIKAP PENEGAK HUKUM TERHADAP TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2009 - Agung Asmara (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT In the application of the cumulative punishment is divided into several phases: the prosecution, the decision stage and the stage of the enforcement or execution. In the lawsuit Narcotics stage, the public prosecutor must consider the criminal provisions in the specific article of the Narcotics Act has been violated. Since the cumulative criminal provisions in the Narcotics Act is not specified on replacement confinement criminal penalties which are related to the defendant and therefore wealth difficulties in terms of execution, the prosecutor in the prosecution case Narcotics also included on the fine substitute imprisonment. Whereas in the case of Narcotics verdict stage, the judge is bound to the indictment prosecutors, legal evidence in court and is tied to the criminal provisions of the Narcotics Act. As for the implementation phase of a court decision (execution), the implementation of the decision is divided into three, namely: the implementation (execution) imprisonment, execution (execution) criminal fines and implementation (execution) imprisonment for a fine substitute.